PENGARUH ATRIBUT DEWAN DIREKSI TERHADAP KEBIJAKAN PEMBAYARAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) - Zulfikri Dwi Sahputra; Syarifah Rakhmawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to determine the effect of the Attributes of the Board of Directors on the Dividend Payment Policy in Manufacturing companies listed on the Indonesia Stock Exchange (IDX). Attributes of the Board of Directors are seen in the variables of Gender Diversity of the Board of Directors, Size of the Board of Directors, Term of Office of the Board of Directors, and Age of the Board of Directors. This study uses panel data with 87 manufacturing companies for the 2016-2020 period. The analytical model used is multiple linear regression analysis. The sampling technique used was purposive sampling with the EGLS Panel analysis method (cross-section random effect). The results of this study partially show that board gender diversity, board size, board tenure have a positive and significant effect on dividend policy and board age has a negative effect on dividend policy in manufacturing companies.